(untitled) (Research, Society and Development, 2018)
Current research has shown great interest in microalgae for their ability to capture CO2 from the atmosphere, harmful gas to the environment and also to store bio-oil with high added value. This oil can be constituted of polyunsaturated fatty acids of Omega 3 and Omega 6. In addition to having as a scenario the bibliometric, a statistical tool that allows to map and generate different indicators of treatment and managements of information and knowledge. Thus, a quantitative analysis of the articles found in the Web of Science database was carried out and a qualitative analysis was carried out, allowing highlighting the importance of the study of this technique. For example, France and Portugal as the country with the largest number of publications, spreading to several countries in different continents. Finding a rise in the number of articles published in recent years, showing the growing interest in microalgae bio-oil.